Empowering Maternal Healthcare through IoT- Driven Long-Term Monitoring: System Architecture and Assessment - Panchal, Dipali; Vaghela, Krunal (Journal of Neonatal Surgery, 2025)
During pregnancy, it is crucial to monitor maternal health to ensure the well-being of both the mother and the unborn baby. Numerous studies conducted thus far have presented a range of maternal health monitoring systems. However, these studies tend to concentrate on particular health concerns and frequently depend on limited-term data- gathering approaches like questionnaires. Furthermore, there is a lack of long-term studies evaluating the requirements and challenges of continuous monitoring. Our team has successfully developed an advanced system that utilizes cutting-edge Inter- net-of-Things (IoT) technology to continuously monitor maternal health both before and after childbirth. This cutting-edge system integrates various data collection mechanisms to precisely record crucial health metrics, including stress levels, sleep pat- terns, and physical activity. We conducted a comprehensive study with actual pregnant women from the Vadodara region of Gujarat State, India, to validate the effectiveness of our system. Our extensive research has unequivocally demonstrated the practicality, energy efficiency, and the data reliability of this system we have established. This system has been proven to be highly effective in monitoring the health of expectant mothers for the entire duration of their nine-month pregnancy. Our maternal health monitoring system, utilizing IoT technology, offers an exceptional framework for ongoing monitoring throughout both pregnancy and the postpartum period. Rest assured that our system is the ultimate solution for monitoring maternal health. It has been implemented and evaluated, providing valuable insights into its feasibility, energy efficiency, and data reliability. This positions it as a strong candidate for improving maternal care and seamless integration with existing healthcare systems.